La sobreprotección y su relación con el lenguaje oral de los niños y niñas de primer grado de educación general básica de la escuela “Galo Vela Alvarez” del cantón Quito, provincia de Pichincha, periodo lectivo 2013-2014”. Lineamientos propositivos - Tigre León, Zoila Lucia (2014)
This thesisrefers to:THE OVERPROTECTION AND ITS RELATIONSHIPWITH BASIC GENERAL EDUCATION FIRST DEGREE CHILDREN ORAL LANGUAGE "GALO VELAALVAREZ" SCHOOLQUITO CANTON, PICHINCHAPROVINCE, PERIOD2013-2014". The general objectiveof thisresearchwas: To analyze the overprotectionand its relation totheOralLanguagechildrenFreshmanBasic General Education first degree children oral Language. The methods used were: Scientist, Inductive,Deductive, Analytic, Synthetic,Qualitative-Quantitative, Descriptive andStatisticalModel;the techniqueswereappliedtoa Parent’s surveysto establishthe causes ofOverprotection; likewisewe used atest(ELO), the same who helpedevaluate theChildren OralLanguage. Applicationof the surveywas taken as referencequestions 8and 9,it is concluded that: 83% parents surveyedsaid theyaren’t consideredoverprotectiveand 17% when considering overprotective.28% ofsurveyedparentsoverprotect theirchildren becausethey do not wantto sufferwhat theyhave suffered, 15% istoprove to be agood parent, 11% because it is easierto educateconsentbeforediscipline, 10%is to give them thelove thatgavethem,10%because they workall day andthe timethey spend withhim or heristo pleaseall, 8% is asingle parent, 7%because his parentsraised himwell, 4% want to giveall thatyoumissthemin childhood, 3% todo with themwhat theycould not have doneit,while3% thatis an only childordaughterand 1%to have agood performance. TestApp(ELO) to assess theOralLanguagedetermines that: 76% ofthechildren assessedscoreobtained95 to 99that corresponds to therating ofVery Highon theOralLanguage, 16% obtainedthescore of40 to 60which corresponds to themeanrating of6%obtainedscoresof75 to 90corresponding toHigh, 2% obtainedscoresof65 to 70corresponding toMedium High